Pengaruh Pemahaman Akuntasi, Insentif Pajak, dan M-Pajak terhadap Kepatuhan Pelaporan Pajak UMKM di Kabupaten Gunungkidul - Aan Pajri Nurtiasmoko; Sri Ayem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes are one of Indonesia's largest sources of income. The number of MSMEs continues to increase every year, which should have an impact on increasing state revenues. Lack of socialization, low tax participation in the MSME sector. MSMEs' low tax participation results from low literacy and understanding of tax calculations. Tax arrears in Gunungkidul Regency have improved due to the Covid-19 pandemic. This study will test whether understanding accounting, tax incentives, M-Tax have an effect on MSME tax reporting compliance. This study used 80 MSME respondents. The questionnaire was administered online and analyzed using IBM SPSS 25 to prove the hypothesis. The results show that understanding accounting and M-Tax influences MSME tax reporting compliance, tax incentives have no effect on MSME tax reporting compliance. The implications for the government as a basis for policy making and support for MSMEs.